Pendidikan Karakter Pancawaluya: Integrasi Nilai-Nilai Budaya Sunda dalam Penguatan Generasi Unggul di Jawa Barat - Sofyan, Fitri Silvia; Sundawa, Dadang; Wutsqah, Urwatul (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
Moral degradation and character crisis among students are serious challenges in the contemporary Indonesian education system. The phenomenon of violence in school environments, intolerance, and declining social empathy demonstrate the urgency of strengthening contextual character education based on local wisdom. This article examines the implementation of Pancawaluya Character Education as a character development model based on Sundanese cultural values in West Java. Using the Systematic Literature Review (SLR) method, this study analyzes Pancawaluya integrated into five core values: Cageur (physically and mentally healthy), Bageur (noble character), Bener (honest and responsible), Pinter (intelligent and wise), and Singer (creative and innovative). The results of the study indicate that Pancawaluya has strong coherence with the competency framework of the Global Inner Development Goals (IDGs) and the Four Pillars of Education of UNESCO, while maintaining local cultural identity through the principles of silih asih, silih asah, silih asuh. The implementation of Pancawaluya through strategies within educational units, classrooms, and family-community partnerships demonstrates significant potential in shaping "Manusa Waluya," a complete, character-driven, and globally competitive generation, while remaining rooted in the noble values of Sundanese culture.